Do colorectal cancer patients diagnosed as an emergency differ from non-emergency patients in their consultation patterns and symptoms?: a longitudinal data-linkage study in England - Renzi, C.; Lyratzopoulos, G.; Card, Timothy R.; Chu, T.; Macleod, U.; Ratchet, B. (Cancer Research UK, 2016)
Background: More than 20% of colorectal cancers are diagnosed following an emergency presentation. We aimed to examine pre-diagnostic primary care consultations and related symptoms comparing patients diagnosed as emergencies with those diagnosed through nonemergency routes. Methods: Cohort study of colorectal cancers diagnosed in England 2005-06 using cancer registration data individually linked to primary care data (CPRD/GPRD), allowing a detailed analysis of clinical information referring to the 5-year pre-diagnostic period. Results: Emergency diagnosis occurred in 35% and 15% of the 1029 colon and 577 rectal cancers. ‘Background’ primary care consultations (2-5 years before diagnosis) were similar for either group. In the year before diagnosis, more than 95% of emergency and non-emergency presenters had consulted their doctor, but emergency presenters had less frequently relevant symptoms (colon cancer: 48% versus 71% (p<0.001); rectal cancer: 49% versus 61% (p=0.043)). ‘Alarm’ symptoms were recorded less frequently in emergency presenters (e.g. rectal bleeding: 9% versus 24% (p=0.002)). However, about 1/5 of emergency presenters (18% and 23% for colon and rectal cancers) had 'alarm' symptoms the year before diagnosis. Conclusions: Emergency presenters have similar ‘background’ consultation history as nonemergency presenters. Their tumours seem associated with less typical symptoms, however opportunities for earlier diagnosis might be present in a fifth of them.